2019
DOI: 10.1016/j.cmet.2019.07.016
|View full text |Cite|
|
Sign up to set email alerts
|

Alternate Day Fasting Improves Physiological and Molecular Markers of Aging in Healthy, Non-obese Humans

Abstract: Caloric restriction and intermittent fasting are known to prolong life-and healthspan in model organisms, while their effects on humans are less well studied. In a randomized controlled trial study (ClinicalTrials.gov identifier: NCT02673515), we show that 4 weeks of strict alternate day fasting (ADF) improved markers of general health in healthy, middle-aged humans while causing a 37% calorie reduction on average. No adverse effects occurred even after >6 months. ADF improved cardiovascular markers, reduced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
242
3
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(302 citation statements)
references
References 67 publications
(91 reference statements)
11
242
3
14
Order By: Relevance
“…The survey exposed that food intake was the key course of weight change, increasing food intake may resulting weight gain, and decreasing food intake may leading to weight loss, which coincided with the current clinical research on reducing food intake through alternate fasting to achieve weight loss (19,20). Ideal and satisfaction of weight, daily steps and BMI changes of participants.…”
Section: Discussionmentioning
confidence: 91%
“…The survey exposed that food intake was the key course of weight change, increasing food intake may resulting weight gain, and decreasing food intake may leading to weight loss, which coincided with the current clinical research on reducing food intake through alternate fasting to achieve weight loss (19,20). Ideal and satisfaction of weight, daily steps and BMI changes of participants.…”
Section: Discussionmentioning
confidence: 91%
“…The health benefits of intermittent fasting on aging, antioxidant stress, metabolism and cardiovascular disease have been demonstrated in human and animal studies [18,[24][25][26][27], but its effect on gut microbiota remains largely unclear. In our study, we found 30 days of daily fasting (16 h fasting) led to significantly increased level of Akkermansia and deceased level of Alistipes.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to combat metabolic inflammation associated with alterations in the gut microbiome may include time-restricted feeding [105], diets rich in fibers [106] and restricted in carbohydrates [107,108], and further n-3 PUFA supplementation [109]. In addition, kynurenic acid, a downstream metabolite of the kynurenine pathway that is activated by exercise training, has been shown to promote the expression of genes involved in lipid metabolism and anti-inflammatory immune responses in adipose tissue [110].…”
Section: Gut Microbiota and Probioticsmentioning
confidence: 99%